Imago Dei and Soul: How to Justify A Special Position of Humans? - May, Andreas (KAMASEAN: Jurnal Teologi Kristen, 2024)
Today, it is highly controversial in Western societies, that humans are made in the image of God (“imago Dei”). This article is looking for a unique feature of man that can justify his special position. The methodological approach consists of contrasting research results and social developments documented in current publications with modern theological and philosophical publications. Our intelligence and the fact that we are self-aware are no longer sufficient as a unique human feature, because biology, palaeoanthropology and computer technology call it into question. This article shows that the soul remains the unique feature of the human being. But often no clear distinction is made between the transcendent soul and the immanent mind. The article therefore emphasises that the soul is transcendent, eternal and a gift of God from transcendence. In order to achieve this, we must abandon the bipartition of man into body and soul and accept the tripartite division of man into body, mind and soul. The transcendence of the soul provides us with a justification for why humans and only humans are “imago Dei”. This gives us a basis for claiming the right of every human being for life and personal realisation.